Indoor and outdoor road traffic noise and incident diabetes mellitus: Results from a longitudinal German cohort study. Issue 1 (February 2019) - Ohlwein, Simone; Hennig, Frauke; Lucht, Sarah; Matthiessen, Clara; Pundt, Noreen; Moebus, Susanne; Jöckel, Karl-Heinz; Hoffmann, Barbara
Abstract : Background: Road traffic noise affects a large number of people in urbanized areas. Recent epidemiological evidence indicates that environmental noise exposure may not only be associated with cardiovascular but also with cardio-metabolic outcomes. This prospective cohort study investigated the effect of outdoor and indoor residential road traffic noise on incident type 2 diabetes mellitus (T2DM). Methods: We used data from 3, 396 participants of age 45–75 years of the Heinz Nixdorf Recall study being non-diabetic at baseline (2000–2003). T2DM was defined via blood glucose level, incident intake of an anti-diabetic drug during follow-up or self-reported physician diagnosis at follow-up examination (2005–2008). Weighted 24-h (Lden ) and night-time (Lnight ) mean road traffic noise was assessed according to the European Union directive 2002/49/EC. Road traffic noise exposure indoors was modeled taking into account the participants' room orientation, ventilation behavior and window insulation (n = 2, 697). We applied Poisson regression analyses to estimate relative risks (RRs) of incident T2DM, adjusting for demographic characteristics, lifestyle factors, and air pollution exposure (NO2 or PM2.5 ). Results: A 10-dB(A) increase in outdoor road traffic noise (Lden ) was associated with an RR of 1.09 (95% confidence interval, 0.96–1.24) for T2DM in the fully adjusted model. Models including PM2.5 or NO2 yielded RRs of 1.09 (0.96–1.24) and 1.11 (0.97–1.27), respectively. In analyses with road traffic noise (Lden ) exposure indoors, we observed similar RRs with smaller confidence intervals (1.11 [1.01–1.21]). Conclusions: Our analyses suggest that long-term exposure to indoor and outdoor road traffic noise may increase the risk of developing T2DM, independent of air pollution exposure. Abstract : Supplemental Digital Content is available in the text.